2018
DOI: 10.1016/j.rpor.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Absorption ratio of treatment couch and effect on surface and build-up region doses

Abstract: The results showed that the carbon fiber couch increased surface dose during posterior irradiation. Therefore, the skin-sparing effect of the high energy beams was decreased. If the effect of couch is not considered, it may cause significant differences at dose which reaches the patient and may cause tissue problems such as erythema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Due to the large attenuation of the radiation at specific angles and positions of the treatment couch [7], without suitable couch modeling, the dose received by the patient during the treatment process is lower than the planned dose, reducing treatment effectiveness. Studies have shown that the treatment couch can increase the dose to the skin and may cause serious damage [8][9][10]. With the widespread use of IMRT technology, the complex multileaf collimator (MLC) motion puts forward higher requirements for the verification of the planned dose.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large attenuation of the radiation at specific angles and positions of the treatment couch [7], without suitable couch modeling, the dose received by the patient during the treatment process is lower than the planned dose, reducing treatment effectiveness. Studies have shown that the treatment couch can increase the dose to the skin and may cause serious damage [8][9][10]. With the widespread use of IMRT technology, the complex multileaf collimator (MLC) motion puts forward higher requirements for the verification of the planned dose.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that to contour immobilization devices in a TPS is not necessary, because these devices consist of lowdensity material. However, many studies have shown that immobilization devices may influence the dose distribution in a patient (Chen et al 2018;Tuğrul 2018;Gerig et al 2010;v et al 2002;v et al 2017;Wu et al 2006). However, studies examining this effect using different algorithms are limited in the literature.…”
Section: Introductionmentioning
confidence: 99%